Serological examination using lipoarabinomannan antigen for the diagnosis of pulmonary tuberculosis - Ning Rintiswati, Ning Rintiswati (Universitas Gadjah Mada, 1997)
Tuberculosis is still an important public health problem, especially in the developing countries. Efforts have been made to overcome the problem. However, tuberculosis control program has not yet been satisfactory. This is due to various factors which might affect the development of the disease, including poverty, lack of understanding about the disease, relatively long period of time needed for treatment as well as increasing number of resistant strain against antimycobacterial drugs. One of the most important ways in controlling tuberculosis is case finding. An acurate and reliable diagnostic kit is also needed to establish the diagnosis. In this study we evaluated sensitivity and specificity of lipoarabinomannan as antigen for serological examination (Mycodot) in patients suspected of having tuberculosis. Using culture of sputum as gold standard, we observed that the sensitivity and specificity of Mycodot were 50% and 70.59%, respectively. This sensitivity was much lower than that of previous study. Interestingly, we found that 47,55% of suspected cases were negative for all three different examinations (acid fast, culture and Mycodot). With respect to this finding it is suggested that better and proper microbiological examination is required to diagnose patient with suspected tuberculosisKey words: Tuberculosis - Lipoarabinomannan - Mycodot - Acid fast - Mycobacterial Culture